Effect of Radiation and Surface Recombination on the Characteristics of an Ion-Implanted GaAs MESFET - Mishra S.; Singh V.K.; Pal B.B. (My University, 2025)
The effect of optical radiation and surface recombination on the characteristics of an ion-implanted GaAs MESFET is studied analytically in the below-pinchoff region. Results show that optical radiation significantly enhances the drain-source current of the GaAs MESFET when only electron-hole pair generation is considered. However, the surface recombination, which in turn results in a gate leakage current, reduces the drain-source current depending on the density of trap centers. The threshold voltage is found to decrease under the normally off condition and increase under the normally on condition due to photogenerated carriers. The surface recombination reverses the effect, i.e., threshold voltage increases under the normally off condition and decreases under the normally on condition, with the increase in the trap center density at a particular ion dose compared to those cases where the effect of recombination is not considered. © 1990 IEEE